Computer-Assisted Intervention (CAI) To Enhance Mathematical Learning Of Autistic Students: A Case Study In Melaka - Ananta, Gede Pramudya; Sedek, Muliati; Shahbodin, Faaizah; Che Amran, Aliza; Ruslan, Siti Nur Azrreen (GIAP Journals, 2019)
Purpose of the study: To evaluate the efficacy of a CAI called MathTutor in helping autistic students to learn addition in mathematics. Methodology: A pre-post-test experimental model was employed in the study. The study participants included three autistic male students who possessed all the prerequisite skills. Main findings and novelty: The study participants were found to have been benefitted which indicates that MathTutor improves their learning abilities as an effective instructional strategy. The use of CAI enabled the participants to memorise their lessons and actively take part during the entire lesson. Applications of this study: The study is beneficial for people involved in caring for autistic students with the help of computer assisted application. This will ease the burden of the carer takers of autistic children in dealing with their conditions while at the same enabling them to navigate the world.